MANAJEMEN ASET DALAM PENGELOLAAN TANAH DAN BANGUNAN PADA BPKAD KABUPATEN SUMBAWA PROPINSI NTB: Asset Management in the Administration of Land and Buildings at the Regional Financial and Asset Management Agency (BPKAD) of Sumbawa Regency, West Nusa Tenggara Province - Fariantin, Erviva; Setiawati, Elvina; Oktavia, Yusi Faizathul; Asdiansyuri, Ulfiyani (Ganec Swara, 2025)
This study aims to examine asset management in the administration of land and buildings at the Regional Financial and Asset Management Agency (BPKAD) of Sumbawa Regency, West Nusa Tenggara Province (NTB). The respondents of this study are all employees at the BPKAD office of Sumbawa Regency, NTB Province. The research sample was selected using purposive sampling with criteria based on employees directly involved in land and building asset management. Data were collected through the distribution of questionnaires to respondents at the BPKAD office of Sumbawa Regency. The results of the study indicate that the management of land and building assets at BPKAD Sumbawa Regency has been carried out in accordance with Article 4, Paragraph 2 of the Minister of Home Affairs Regulation No. 17 of 2007. This is evident from the fact that the Sumbawa Regency Government has received an Unqualified Opinion (WTP) from the Audit Board of Indonesia (BPK) for ten consecutive years and has been designated as a member of the Heritage City Network. However, there are still aspects that are lacking or have not been fully optimized in the implementation of asset management work stages